WAREL; A System for Retrieval of Clinical Data Considering the Course of Diseases - Dorda, W. G. (Methods of Information in Medicine, 1989)
Medical research requires a general survey on patients’ records in order to recognize medical risk factors for different groups of patients. A clinical data bank with a retrieval system for specific groups of patients could assist medical research.The requirements for an evaluation system of clinical data banks are demonstrated. Stress is laid on the problems of selecting a group of patients concerning the course of their diseases. The retrieval system “WAREL” - WAREL stands for Wiener Allgemeines Relationen-Schema (Vienna General Relational System) - offers a possible solution to these problems. Synchronization operators allow to specify the desired sequence of single events within the course of an illness. In order to define the requested course of illness not only units of time (e. g., hours or days) can be used but also individual time units (e. g., length of individual illness or pregnancy).
Keywords: Clinical Databases; Synchronization Operators; Retrieval; Query Methods